2021
DOI: 10.3389/fpubh.2021.653565
|View full text |Cite
|
Sign up to set email alerts
|

Introducing and Implementing HIV Self-Testing in Côte d'Ivoire, Mali, and Senegal: What Can We Learn From ATLAS Project Activity Reports in the Context of the COVID-19 Crisis?

Abstract: Background: The ATLAS program promotes and implements HIVST in Côte d'Ivoire, Mali, and Senegal. Priority groups include members of key populations—female sex workers (FSW), men having sex with men (MSM), and people who use drugs (PWUD)—and their partners and relatives. HIVST distribution activities, which began in mid-2019, were impacted in early 2020 by the COVID-19 pandemic.Methods: This article, focusing only on outreach activities among key populations, analyzes quantitative, and qualitative program data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Moreover, the descriptive data showed that a decrease in conventional testing occurred in all districts, including those not covered by ATLAS activities, this is linked to the fact that PEPFAR’s testing strategies are revised annually and favoring more targeted approaches. 26 Our results suggest that ATLAS HIVST distribution allowed to maintain access to HIV testing in its implementation districts despite the slowdown observed in Q2 2020 when governmental COVID-19 measures were introduced. In fact, the first results of the ATLAS project have shown that HIVST distribution activities among KPs could be easily adapted, including in the context of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the descriptive data showed that a decrease in conventional testing occurred in all districts, including those not covered by ATLAS activities, this is linked to the fact that PEPFAR’s testing strategies are revised annually and favoring more targeted approaches. 26 Our results suggest that ATLAS HIVST distribution allowed to maintain access to HIV testing in its implementation districts despite the slowdown observed in Q2 2020 when governmental COVID-19 measures were introduced. In fact, the first results of the ATLAS project have shown that HIVST distribution activities among KPs could be easily adapted, including in the context of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 69%
“…Our results suggest that ATLAS HIVST distribution help maintain access to HIV testing in its implementation districts despite the slowdown observed in Q2 2020 when governmental COVID-19 measures were introduced. In fact, a main takeaway from the ATLAS project is that HIVST distribution activities among KPs can be easily adapted, including in the context of the COVID-19 pandemic [21]. Due to its confidential nature, HIVST could overcome several structural barriers for HIV diagnoses -such as stigma and opportunity costs -and create new approaches to reach first-time testers and boost HIV retesting for KPs, therefore improving access to HIV testing overall.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that ATLAS HIVST distribution help maintain access to HIV testing in its implementation districts despite the slowdown observed in Q2 2020 when governmental COVID-19 measures were introduced. In fact, a main takeaway from the ATLAS project is that HIVST distribution activities among KPs can be easily adapted, including in the context of the COVID-19 pandemic [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) . Program evaluations conducted in Europe, North America, Asia, and Africa suggested that most health care and harm reduction services for PWID, including HIV testing ( Frost et al., 2021 ; Htun Nyunt et al., 2021 ; Kra et al., 2021 ), HIV treatment ( Mistler et al., 2021 ), access to sterile injection equipment ( Croxford et al., 2021 ; Van Hout et al., 2021 ), and post-overdose care in emergency departments ( Collins et al., 2021 ), were negatively affected by the pandemic, though some programs were able to adapt quickly and innovate new forms of service delivery ( Van Hout et al., 2021 ; Wenger et al., 2021 ). Qualitative research exploring how the COVID-19 pandemic has shaped the lived experience of PWID remains limited to studies of overdose risks and the necessity of harm reduction services during pandemic conditions in parts of the United States and Canada ( Perri et al., 2021 ; Russell et al., 2021 ; Stack et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%